Determining of unknown functions of different arguments in minor coefficient and right-hand side of semilinear ultraparabolic equation - Protsakh, N.P.; Flyud, V.M. (Carpathian Mathematical Publications, 2020)
In this paper, we consider the inverse problem for semilinear ultraparabolic equation. The equation has two unknown functions of different arguments in its minor coefficient and in right-hand side function. The sufficient conditions of the existence and the uniqueness of solution on some interval [0,T], where T depends on the coefficients of the equation, are obtained.